EVALUASI BANTUAN PANGAN NON TUNAI DI KECAMATAN CERME KABUPATEN GRESIK - Muhammad Luqman Abdul Aziz; Kalvin Edo Wahyudi (Halu Oleo University, 2023)
This research aims to determine the level of success of the Non-Cash Food Assistance Program (BPNT) in Cerme District, Gresik Regency. The research method used in this research is qualitative descriptive research. The research focus of this study is to describe the evaluation of the Non-cash Food Assistance Program (BPNT) in Cerme District, Gresik Regency. Data collection techniques in this research include interviews, observation, documentation and literature study. The data sources used are primary and secondary data sources. The results of research on the Evaluation of the Non-Cash Food Assistance Program (BPNT) in Cerme District, Gresik Regency, namely: that the BPNT program is useful in helping meet their economic needs even though the assistance provided is not commensurate with their food needs until the following month and assistance from last year was given alternately in the form of goods or given in cash. This is because the BPNT program plays a more or less significant role in meeting their daily needs, and also provides them with sufficient relief in meeting the food needs of underprivileged communities. Based on the conclusions, the Non-Cash Food Assistance Program (BPNT) in Cerme District, Gresik Regency, can be said to be quite successful.